Geographical Marginality in Slovenia from the Point of Demographical Indicators - Pelc, Stanko (Journal for Geography, 2006)
We start the paper with a terminological discussion about globalization and geographical marginality. Then we present an analysis that intends to find out whether the demographic data at municipal level can reveal us marginal regions (municipalities). We devided all municipalities according to their centrality into the group of predominantly central and predominantly peripheral. We calculated 5 demographic indicators and according to the average value defined municipalities that were essentially different (potentially marginal). The analysis shows that demographic indicators are not reliable and not an appropriate tool for the definition of marginal regions.
Keywords: geographical marginality; globalization; demographic indicators; Slovenia